Hubungan Moderasi Antara Kepuasan Pelanggan Dan Pembelian Ulang Terhadap Barang E-Commerce Yang Dipengaruhi Oleh E-Wom - Elca Vebi Anggelyani; Widarto Rachbini (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to explore how customer satisfaction can moderate the relationship between e-word of mouth (e-WOM) and e-commerce repurchase intentions. In today's digital era, e-WOM has become one of the important factors that influence consumer purchasing decisions. The method used surveyed e-commerce customers and analyzed the data using moderation regression. The results show that customer satisfaction is an important factor influencing the positive effect of e-WOM on repurchase intentions. These results provide e-commerce businesses with important knowledge to create effective marketing strategies and improve customer experience. It is hoped that this work will serve as a reference source for further research on the way these variables interact in the context of e-commerce.